Effekter av klimatförändringar på växtplankton i subarktiska och alpina sjöar - Lundström, Matilda (SLU/Dept. of Aquatic Sciences and Assessment, 2019)
The aim of this report was to determine how the climate change affects the ecosystems in alpine and subarctic lakes in Sweden. This was done by analyzing data from environmental monitoring of 14 subarctic and alpine lakes that was part of the national time-series lake monitoring program. The research questions were: How has climate and the water chemical composition of the lakes changed and how has this affected biomass and biodiversity of the phytoplankton in the examined lakes? The climate variables analyzed were the annual average atmospheric temperature and the annual precipitation from year 1993 to 2017. Data were retrieved from the Swedish Metrological and Hydrological Institute (SMHI). For analyzes of the water chemical composition the pH-value, the total amount of organic carbon (TOC) and the total amount of phosphorous were examined. The biological variables used in this report were the total mass of phytoplankton, the biodiversity of the phytoplankton and changes in biovolumes of each phytoplankton class. The data for the variables of the water chemical composition and biology covers the years 1993-2018 and were retrieved from the Swedish University of Agriculture Science (SLU). Testing for trends and correlations were made in Excel and JMP. The results show an increase in annual average temperature but no trends for annual precipitation was detected. A strong decrease was detected for amount of phosphorus along with an increase in pH. Despite the major decrease in phosphorus a significant increase of the biovolume of phytoplankton was seen. No significant trends were detected for TOC or biodiversity. No correlations between trends for the climate and the water chemical composition or the biomass and biodiversity of the phytoplankton was found. There was however an indication for a possible correlation between temperature and amount of phosphorus. Nor were there any correlations between trends for the water chemical composition and the biomass and biodiversity of the phytoplankton. Pahajärvi differ from the rest of the lakes with a positive trend for amount of phosphorus and a correlation with trends in phosphorus and biovolume phytoplankton. This study concludes that further research should be done to examine why there is a negative trend for phosphorus in lakes and what this decrease might mean to the ecosystems in the Swedish subarctic and alpine lakes in the future. It would also be interesting to look further in to Pahajärvi`s positive trend in phosphorus and to examine if any patterns can be seen for type of precipitation.